Prioritising action on occupational carcinogens in Europe: a socioeconomic and health impact assessment - Cherrie,JW; Hutchings,S; Ng,MG; Mistry,R; Corden,C; Lamb,J; Jimenez,AS; Shafrir,A; Sobey,M; van,Tongeren M; Rushton,L (British Journal of Cancer, 2017)
background: Work-related cancer is an important public health issue with a large financial impact on society. The key European legislative instrument is the Carcinogens and Mutagens Directive (2004/37/EC). In preparation for updating the Directive, the European Commission commissioned a study to provide a socioeconomic, health and environmental impact assessment.methods: The evaluation was undertaken for 25 preselected hazardous substances or mixtures. Estimates were made of the number of cases of cancer attributable to workplace exposure, both currently and in the future, with and without any regulatory interventions, and these data were used to estimate the financial health costs and benefits.results: It was estimated that if no action is taken there will be >700 000 attributable cancer deaths over the next 60 years for the substances assessed. However, there are only seven substances where the data suggest a clear benefit in terms of avoided cancer cases from introducing a binding limit at the levels considered. Overall, the costs of the proposed interventions were very high (up to euro34 000 million) and the associated monetised health benefits were mostly less than the compliance costs.conclusions: The strongest cases for the introduction of a limit value are for: respirable crystalline silica, hexavalent chromium, and hardwood dust.